The Relationship Between Mother’s Support to the Development Level of Preschool-Age Children - Dwi Hastuti; Retna Ningsih; Fifi Fauziah; Siti Nurbayanti; Ibrahim Bola (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aim: The prevalence data for growth and development disorders is increased by 28.7%, and Indonesia being the third highest in Southeast Asia. The influence of family support, especially from the mother, is very influential on the child's development because the mother's encouragement is very influential on the child's success in achieving development according to the stages. This study aims to analyze the relationship between maternal support and the level of development of preschool children in Daya Wanita Kindergarten, Sumedang. Methods: The research design used was an analytic survey with a cross-sectional approach. The number of samples used is 70 respondents (35 children and 35 mothers). This study used a purposive sampling technique and the developmental pre-screening questionnaire (KPSP) to measure the mother's support using a Guttman scale with two choices of answers that support and do not support. Result: Univariate data analysis with frequency distribution technique and bivariate using Chi-Square test. The results showed that out of 35 children, 20 children had appropriate development (57.1%), ten children had doubtful development (28.6%), and five children had abnormal development (14.3%). Most of the children received support from their mothers. As many as 22 people (62.9%) and 13 children did not get proper support (37.1%). There is a significant relationship between the mother's support and preschool-age children's development level (p-value = 0.007). Conclusion: This study showed a relationship between mothers' support and the development of preschool-age children. Based on this study result is hoped that schools can educate parents about stimulating child development, and parents can facilitate the children's stimulation at home.